Job-hopping behaviour among generation Y: The case for Postgraduate Students in Arshad Ayub Graduate Business School / Aisyah Nazirah Ab Rahman and Nor Hafizah Mohamed Harith - Ab Rahman, Aisyah Nazirah; Mohamed Harith, Nor Hafizah (2021)
Ghiselli (1974) stated job-hopping is also known as a hobo syndrome. Hobe syndrome is an attitude of an employee who will look for a different job, perhaps because of an itch, but hobo also evaluates whether their current job or a new alternative one is more beneficial, which is a rational decision. According to Henrik (2015), employees from Generation Y tend to change positions frequently, and it has been acknowledged that Generation Y turnover intentions result in overt and covert losses such as lost inventions, skills, abilities, and organizational money. Henrik (2015) also stated that the rate of turnover among Generation Y is two times that of Generation X and 4.5 times that of baby boomers and their predecessors, according to research (Lyons et al., 2015). The situation is crucial and needs to be highlighted by stakeholders such as the Ministry of Human Resources, the private sector, and the public. Human Resource Management must recognize the need of hiring and retaining qualified Generation Y personnel to preserve the company's performance.